Strategi dan Kapasitas Inovasi Kebijakan Smart City di Kota Tanjungpinang - Sholeh, Chaerey Ranba; Firman, Firman; Azizi, Okky Rizki; Hafifa, Nur (Bahasa Indonesia, 2024)
The Smart City concept offers solutions for local governments to address urban issues. However, implementing the Smart City vision in various cities encounters challenges. In Tanjungpinang City, the Smart City implementation is fragmented and not well-integrated into governance. This research explores the strategy and capacity of the Tanjungpinang City Local Government in realizing Smart City. A descriptive qualitative method is used to understand Smart City policy innovation in Tanjungpinang. The findings indicate the need for regulations focusing on Smart City and stakeholder collaboration. The government must adopt strategies to enhance capacity in Smart City policy innovation, including strengthening stakeholder coordination, increasing community participation, continuous monitoring and evaluation, and providing adequate budget. With proper strategies and capacity building, Tanjungpinang's Smart City is expected to develop optimally, offering tangible benefits to the community, and establishing itself as a smart, advanced, and cultured city.